THE FACTORS RELATED TO NURSE TIME RESPONSE TO COVID 19 SUSPECT PATIENTS IN HERMINA JATINEGARA HOSPITAL IGD: RESPON TIME PERAWAT PADA PASIEN SUSPEK COVID 19 - Junita Maratur Silitonga; Ria Anugrahwati (Akademi Keperawatan Hermina Manggala Husada, 2021)
The response time or emergency response time is a combination of the response time when the patient arrives at the hospital door until he gets a response from the Emergency Room staff with the service time needed to finish the 5 minute emergency handling process, this study aims to determine the factors Related to the Response Time of Nurses in Suspected Covid 19 Patients in the Emergency Room at the Hermina Jatinegara Hospital. This study used a descriptive research design with a cross-sectional approach. The population in this study were all nurses who served in the emergency room of Hermina Jatinegara Hospital, amounting to 30 people, the sample was taken using a total sampling technique with a total sample of 30 respondents. Data collection using a questionnaire. The data analysis used was univariate and bivariate analysis in the form of chi-square test. Obtained univariate analysis showed that the level of emergency patients in the Emergency Room was more dominated by yellow category emergency patients, namely as many as 13 patients (43.3%), most of the emergency room nurses had the skills of skilled category nurses, namely 19 nurses (63.3%), Generally, the workload of IGD nurses in the light category was 20 nurses (66.7%), and the emergency response time was dominated by nurses whose response time category was good for patients with suspected Covid 19, namely 21 nurses (70.0%). The results of the bivariate analysis showed that there was a relationship between the skills of nurses and the response time of nurses in suspected Covid 19 patients (p value = 0.042), there was a relationship between workload and nurse response time in patients with suspected Covid 19 (p value = 0.030), and there was a relationship between level of emergency with nurse response time in patients with suspected Covid 19 (p value = 0.028). It is hoped that students before carrying out their practice in the emergency room of the hospital can first take part in the BTCLS training so that they can be more skilled in performing emergency care so that the response time of nurses can be better